2022
DOI: 10.1111/1365-2664.14319
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of management and landscape on biological pest control and crop pest infestation in apple orchards

Abstract: Biological pest control, relying on naturally occurring predator–prey dynamics, is considered a key element to achieve more sustainable farming systems. However, the combined effects of local management and landscape factors on communities of natural enemies as well as the cascading effects on pest infestations are rarely addressed, especially in perennial crops. Here, we used Piecewise Structural Equation Modelling (PSEM) to test direct and indirect effects of landscape composition, landscape configuration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Happea et al [36] presented the influence of landscape composition on the abundance and community composition of predatory insects in apple orchards in three European countries and stated that semi-natural habitats enhanced the presence of beneficial insects and their contribution to biological control in fruit crops. Daelemans et al [37] tested the effects of landscape composition on natural enemy communities and the pest control services they provide in apple orchards. Authors suggested that habitat conservation can enhance natural enemies and stimulate pest control.…”
Section: Introductionmentioning
confidence: 99%
“…Happea et al [36] presented the influence of landscape composition on the abundance and community composition of predatory insects in apple orchards in three European countries and stated that semi-natural habitats enhanced the presence of beneficial insects and their contribution to biological control in fruit crops. Daelemans et al [37] tested the effects of landscape composition on natural enemy communities and the pest control services they provide in apple orchards. Authors suggested that habitat conservation can enhance natural enemies and stimulate pest control.…”
Section: Introductionmentioning
confidence: 99%